Nanostructured polypyrrole layers implementation on magnetically navigable 3D printed microdevices for targeted gastrointestinal drug delivery. Issue 4 (26th November 2020) - Bernasconi, R; Favara, N; Fouladvari, N; Invernizzi, M; Levi, M; Pane, S; Magagnin, L
Abstract: The integration of drug releasing polymeric layers on remotely navigable microcarriers is one of the most promising therapeutic strategies for a wide variety of diseases. Thanks to this approach, administration can be precisely targeted to a specific organ, limiting thus side effects and drug waste. In this context, the present work describes the fabrication of 3D printed and wet metallized microdevices intended for targeted drug delivery. Microtransporters are stereolithography printed and coated with a sequence of materials to impart them specific functionalities, like magnetizability and chemical inertness. Polypyrrole (PPy), in both bulk and nanostructured (NA) form, is electrodeposited as top layer to introduce drug delivery properties. Fabricated microdevices are characterized from the morphological and functional point of view. In particular, remote magnetic control and drug release behavior are investigated. Results obtained show a high magnetic maneuverability and good drug loading capability, which is further improved by nanostructuring the PPy layer applied on the surface of the microdevices. A possible application for the magnetically steered carriers described in the present work is localized drug administration for the therapy of many diseases typical of the gastrointestinal tract (e.g. Chron's disease).